Portrait of Indonesian Vocabolary in Writing Skills: Case Study of Darul Maaref School Foundation, Thailand - Nasyahirah, Nurul; Febriyana, Mutia (Journal of Languages and Language Teaching, 2024)
Indonesian is an asset for the Indonesian nation which is always maintained both in the realm of Education and non-Education. Therefore, Indonesian is expected to be global for other countries. Related to this, the Indonesian program for Foreign Speakers (BIPA) as a bridge in introducing the language to the world, namely through four language skills. One of them is writing skills. This study aims to determine students' ability to write Indonesian vocabulary through the  Indonesian teaching program for foreign speakers (BIPA) at Darul Maaref School Foundation, Satun, Thailand. This research method is descriptive qualitative with a case study approach. The results of the study found that written language errors in  Darul Maaref School Foundation students included the use of incomplete sentence types, namely 11 data, word arrangement 3 data, capital letters 96  data, pronouns 1  data, prepositions 15  data, word choice 27  data, spelling 46  data, hyphen 3  data, and affix 2 data. The factors causing students' written language  errors  are  caused by  the influence of spoken language, students have not fully understood Indonesian grammar, students have not carefully  written Indonesian, and BIPA learning has not been effective.  Related to these findings, BIPA teaching materials are needed by emphasizing Indonesian that are in accordance with the rules of Indonesian Spelling  (EBI)  and presented as innovative and fun BIPA learning for students.